Mixed Cryoglobulinaemia Vasculitis Treated with Obinutuzumab in a Patient Allergic to Rituximab - Margarida Gaudencio (SMC MEDIA SRL, 2021)
Cryoglobulinaemia is defined as the presence of cryoglobulins in the serum, which are immunoglobulins that reversibly precipitate and form a gel when the temperature is <37ºC. Autoimmune diseases such as Sjogren’s syndrome, systemic lupus erythematosus and rheumatoid arthritis could be associated with mixed cryoglobulinaemia vasculitis (MCV). The treatment of MCV generally consists of glucocorticoids, cytotoxic agents such as cyclophosphamide, plasmapheresis or anti-CD20 monoclonal antibodies including rituximab. Here, we present a case of a 60-year-old woman who developed type II MCV in the context of overlap autoimmune disease and who has been treated with a new anti-CD20 agent, obinutuzumab.